every equations that the kind ax^2+bx+c=0 have the right to be fixed using the quadratic formula: frac-b±sqrtb^2-4ac2a. The quadratic formula offers two solutions, one when ± is enhancement and one as soon as it is subtraction.

You are watching: X^2+6x+4

This equation is in standard form: ax^2+bx+c=0. Substitute 1 for a, -6 for b, and also -4 because that c in the quadratic formula, frac-b±sqrtb^2-4ac2a.

displaystylex=3+sqrt13,3-sqrt13 Explanation: displaystylex^x-6x-4=0 perfect the square means that us will force a perfect square trinomial top top the left ...

(2x2)-(6x)-4=0 Two remedies were uncovered : x =(3-√17)/2=-0.562 x =(3+√17)/2= 3.562 action by step solution : action 1 :Equation at the finish of step 1 : (2x2 - 6x) - 4 = 0 action 2 : step 3 ...

3x2-6x-4=0 Two remedies were uncovered : x =(6-√84)/6=1-1/3√ 21 = -0.528 x =(6+√84)/6=1+1/3√ 21 = 2.528 action by step solution : action 1 :Equation in ~ the finish of action 1 : (3x2 - 6x) - 4 = 0 ...

The root aredisplaystylefrac3+sqrt295ordisplaystylefrac3-sqrt295 .Explanation: displaystylex=frac-b±sqrtb^2-4ac2a ...

9x2-6x-4=0 Two services were found : x =(6-√180)/18=(1-√ 5 )/3= -0.412 x =(6+√180)/18=(1+√ 5 )/3= 1.079 action by action solution : action 1 :Equation in ~ the end of action 1 : (32x2 - 6x) - 4 = ...

18x2-6x-4=0 Two services were uncovered : x = -1/3 = -0.333 x = 2/3 = 0.667 action by step solution : step 1 :Equation at the end of action 1 : ((2•32x2) - 6x) - 4 = 0 step 2 : action 3 ...

More Items

All equations that the type ax^2+bx+c=0 can be fixed using the quadratic formula: frac-b±sqrtb^2-4ac2a. The quadratic formula offers two solutions, one as soon as ± is addition and one as soon as it is subtraction.

This equation is in standard form: ax^2+bx+c=0. Instead of 1 for a, -6 for b, and also -4 because that c in the quadratic formula, frac-b±sqrtb^2-4ac2a.

Quadratic equations such together this one deserve to be addressed by perfect the square. In bespeak to complete the square, the equation must first be in the form x^2+bx=c.

Divide -6, the coefficient of the x term, by 2 to gain -3. Then add the square of -3 to both political parties of the equation. This step makes the left hand side of the equation a perfect square.

Factor x^2-6x+9. In general, once x^2+bx+c is a perfect square, the can always be factored as left(x+fracb2
ight)^2.

See more: Ple A Financial Statement User Would Determine If A Company Was Profitable

Quadratic equations such together this one deserve to be solved by a brand-new direct factoring technique that walk not need guess work. To use the direct factoring method, the equation have to be in the type x^2+Bx+C=0.

Let r and s be the factors for the quadratic equation such the x^2+Bx+C=(x−r)(x−s) where sum of determinants (r+s)=−B and also the product of determinants rs = C

Two number r and also s sum up come 6 exactly when the typical of the 2 numbers is frac12*6 = 3. Friend can likewise see that the midpoint that r and s coincides to the axis of the contrary of the parabola stood for by the quadratic equation y=x^2+Bx+C. The worths of r and also s are equidistant indigenous the facility by one unknown amount u. Refer r and s with respect to variable u.

EnglishDeutschEspañolFrançaisItalianoPortuguêsРусский简体中文繁體中文Bahasa MelayuBahasa Indonesiaالعربية日本語TürkçePolskiעבריתČeštinaNederlandsMagyar Nyelv한국어SlovenčinaไทยελληνικάRomânăTiếng Việtहिन्दीঅসমীয়াবাংলাગુજરાતીಕನ್ನಡकोंकणीമലയാളംमराठीଓଡ଼ିଆਪੰਜਾਬੀதமிழ்తెలుగు